A Note on the Determinants of UK Business Cycles. - Day, A; Leith, C; Wren-Lewis, S (School of Business and Economics (University of Exeter), 1998)
In their empirical analysis of Real Business Cycle models for the UK, Holland and Scott (1998) find that they cannot reject the proposition that movements in output are largely determined by 'productivity shocks' which are independent of demand side variables, such as interest rates. In this note we extend their work to allow for the impact of financial liberalisation and credit availability. We find that credit availability has had a significant impact on movements in output, and that, when these effects are controlled for, monetary policy variables, including interest rates, also cause output. This is consistent with the conventional view that demand-expansion was the cause of the boom of the late 1980s and appears to reject a RBC interpretation of output movements.